Variations of IGHMBP2 Gene Was Not the Major Cause of Han Chinese Patients With Non-5q-Spinal Muscular Atrophies. (August 2014) - Lin, Xiang; Zhang, Qi-Jie; He, Jin; Lin, Min-Ting; Murong, Shen-Xing; Wang, Ning; Chen, Wan-Jin
Spinal muscular atrophy with respiratory distress type 1 (SMARD1), a notably common form of non-5q-spinal muscular atrophy, can be confused with infantile spinal muscular atrophy and is characterized by the early onset of diaphragmatic palsy and predominantly distal muscle weakness. The defective gene, immunoglobulin mu-binding protein 2 ( IGHMBP2 ), is located on chromosome 11q13-q21. In this study, we screened the IGHMBP2 gene in 53 unrelated Han Chinese non-5q-spinal muscular atrophy patients and 100 healthy controls. Two novel mutations (c.711+1G>C and c.1817G>A) and 5 nucleotide polymorphisms (c.57T>C, c.1554C>T, c.1914G>A, c.2080C>T, and c.2270G>C) were identified. However, only 1 patient harbored the compound heterozygous mutations (c.711+1G>C, c.1817G>A). Furthermore, the homozygous c.2636C>A (p.T879 K) variation, which has been included as a mutation in the Human Gene Mutation Database, was found both in patients and healthy individuals. In conclusion, the IGHMBP2 gene was not found to be a major causative gene linked to Han Chinese non-5q-spinal muscular atrophy patients.